Impact of Living With Scoliosis: A utility Outcome Score Assessment. Issue 2 (15th January 2017) - Aldebeyan, Sultan; Sinno, Hani; Makhdom, Asim; Ouellet, Jean A.; Saran, Neil
Abstract : Study Design: Survey. Objective: The aim of this study was to objectify the burden of adolescent idiopathic scoliosis (AIS) to better advocate for scoliosis care in the future. Summary of Background Data: AIS is a common spinal deformity that can affect individuals on many levels. Patients with big curves usually seek medical advice for surgical correction of their deformity. Methods: Participants completed an online questionnaire to help measure the health burden of AIS. Three utility outcome measures were then calculated. These included the visual analog scale, time trade off, and standard gamble. Student t test and linear regression were used for statistical analysis. Results: One hundred and ten participants were included in the analysis. The mean visual analog scale, time trade off, and standard gamble scores for AIS were 0.77 ± 0.16, 0.90 ± 0.11, and 0.91 ± 0.13, respectively. Factors such as age, sex, income, and level of education were dependent predictors of utility scores for AIS. Conclusion: Our participants demonstrated a significant perceived burden of AIS. If faced with AIS, participants were willing to sacrifice 3.6 years of their lives and undergo a procedure with 9% mortality rate to gain perfect health. Such findings can guide future allocation of resources for better scoliosis care and management. Level of Evidence: 4